2018
DOI: 10.1002/crat.201800002
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Highly Crystalline and Large Scale Monolayer MoS2 by CVD: The Role of substrate Position

Abstract: Monolayer (ML) molybdenum disulphide (MoS2) is of great interest for the scientific community due to its attractive electronic, optoelectronic and mechanical properties. Synthesis of high quality and large size ML MoS2 at low cost is still a challenge. Here, the growth of large area (≈5 × 1 mm2) ML MoS2 on SiO2/Si substrate via chemical vapor deposition (CVD) method is reported. It is shown by changing the substrate position w.r.t. MoO3 precursor, that the quality and size of the ML MoS2 can be drastically tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 49 publications
2
17
0
1
Order By: Relevance
“…The resulting flakes show a large variation in properties depending on their position on the substrate. While this effect is in principle well-known from all CVD processes [40], we observe a strong and quite unusual difference in morphology, and related to this, unexpected changes of vibrational and optoelectronic properties. In particular, while the larger, individual flakes show only weak, trion-dominated PL and appear n-doped and strained, we identified a region with a very high (up to 73 %) coverage of nano-crystalline MoS 2 with negligible strain, p-type doping and a significant PL emission dominated by the A exciton.…”
Section: Discussionsupporting
confidence: 65%
“…The resulting flakes show a large variation in properties depending on their position on the substrate. While this effect is in principle well-known from all CVD processes [40], we observe a strong and quite unusual difference in morphology, and related to this, unexpected changes of vibrational and optoelectronic properties. In particular, while the larger, individual flakes show only weak, trion-dominated PL and appear n-doped and strained, we identified a region with a very high (up to 73 %) coverage of nano-crystalline MoS 2 with negligible strain, p-type doping and a significant PL emission dominated by the A exciton.…”
Section: Discussionsupporting
confidence: 65%
“…Numerical simulations performed by R. A. Vila et al [53] using finite element modelling revealed a decreasing concentration gradient on the surface of the substrate as the distance from the Mo-source increases, and that the concentration gradient pattern is characterized as distinct parabolic growth zones commonly found in experiments [24,29,36,45,49]. Moreover, the presence of such a concentration gradient means that the local Mo:S ratio varies along the length of the growth substrate, increasing the probability of morphology evolutions [53], oxysulfide formations [33,36,48,[50][51][52] and MoS2 domain-shape changes [24]. To make matters worse, experimental factors, such as precursor amount, gas flow rate, substrate position relative to the MoO3 source, growth temperature, geometrical parameters and possibly the spatial distribution of the MoO3 precursor itself, all have an impact on the Mo flux arriving at the substrate.…”
Section: Resultsmentioning
confidence: 96%
“…MoS 2 sheets are grown on a ∼300 nm SiO 2 /Si substrate by chemical vapor deposition method using MoO 3 and sulfur as a precursor at ∼700°C in an argon environment. 39 Raman and PL measurements are carried out with 532 nm laser line, keeping grating at 600 line mm −1 , using WITEC alpha 300 R Raman spectrometer. 40 AFM measurement on monolayer MoS 2 is conducted using a Bruker Multimode 8 AFM system in tapping mode under ambient conditions.…”
Section: Methodsmentioning
confidence: 99%